An excess of prior irritable bowel syndrome diagnoses or treatments in Celiac disease: evidence of diagnostic delay. (July 2013) - Card, Timothy R.; Siffledeen, Jesse; West, Joe; Fleming, Kate M.
Abstract Objective. It is recognized that celiac disease can present with symptoms characteristic of irritable bowel syndrome (IBS) and that a substantial proportion of patients referred to gastroenterologists with these symptoms may have celiac disease. The authors set out to discover how commonly those suffering with celiac disease are misdiagnosed as suffering from IBS and whether such misdiagnosis delays the correct diagnosis. Materials and methods. A case control study using computerized records from the General Practice Research Database was conducted. The authors compared the proportion of patients with celiac disease who had a diagnosis of or had undergone treatment for IBS over a variety of time periods before the diagnosis of celiac disease with the proportion of a matched group without celiac disease who were similarly diagnosed or treated. Results. It was found that 16% of celiac patients had such a prior diagnosis compared to 4.9% of controls (a threefold increased risk of prior IBS; OR = 3.8, 95% CI: 3.6–4.2), and that if one looked at typical treatment for IBS rather than diagnostic codes, 28% of celiac patients appeared to have been treated compared to 9% of controls. Many of the diagnoses of IBS occurred within the last year before diagnosis of celiac disease, but there was a clear excess of IBS even 10 years earlier. Conclusions. In contemporary UK practice, it is likely that at least some patients with celiac disease spend many years being treated as having IBS. Following guidelines to test serologically for celiac disease will minimize this problem.